2021
DOI: 10.1186/s13690-021-00561-z
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life of multiple sclerosis patients: a European multi-country study

Abstract: Background Inconsistent use of generic and disease-specific health-related quality of life (HRQOL) instruments in multiple sclerosis (MS) studies limits cross-country comparability. The objectives: 1) investigate real-world HRQOL of MS patients using both generic and disease-specific HRQOL instruments in the Netherlands, France, the United Kingdom, Spain, Germany and Italy; 2) compare HRQOL among these countries; 3) determine factors associated with HRQOL. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 45 publications
2
20
0
Order By: Relevance
“…Patient characteristics at baseline were a hypothetical cohort of 1000 Dutch RRMS patients. The baseline characteristics (mean starting age of the cohort was set at 35 years old, a 3:1 female to male ratio, and the distribution of disability status based on the patient’s current first-line DMT status) reflect the data collected through an online HRQOL survey in the Netherlands [ 14 ]. The disability status was measured using the Expanded Disability Status Scale (EDSS, a measure that quantifies disability on a scale from 0 [no disability] to 10 [death] [ 15 ]), and the distribution was as follows: EDSS 0 (14%), EDSS 1 (29%), EDSS 2 (29%), EDSS 3 (0%), EDSS 4 (0%), EDSS 5 (14%), EDSS 6 (14%), EDSS 7–9 (0%).…”
Section: Methodsmentioning
confidence: 99%
“…Patient characteristics at baseline were a hypothetical cohort of 1000 Dutch RRMS patients. The baseline characteristics (mean starting age of the cohort was set at 35 years old, a 3:1 female to male ratio, and the distribution of disability status based on the patient’s current first-line DMT status) reflect the data collected through an online HRQOL survey in the Netherlands [ 14 ]. The disability status was measured using the Expanded Disability Status Scale (EDSS, a measure that quantifies disability on a scale from 0 [no disability] to 10 [death] [ 15 ]), and the distribution was as follows: EDSS 0 (14%), EDSS 1 (29%), EDSS 2 (29%), EDSS 3 (0%), EDSS 4 (0%), EDSS 5 (14%), EDSS 6 (14%), EDSS 7–9 (0%).…”
Section: Methodsmentioning
confidence: 99%
“…For a tool to effectively identify the progression of MS, multiple aspects of the disease should be considered, such as aspects of daily living and patient clinical history [ 42 , 43 , 44 ]. Such aspects are frequently overlooked, though research has shown that they provide neurologists with a deeper understanding of their patient’s health status [ 42 , 43 ].…”
Section: The Importance and Potential Challenges Of Early Identificat...mentioning
confidence: 99%
“…For a tool to effectively identify the progression of MS, multiple aspects of the disease should be considered, such as aspects of daily living and patient clinical history [ 42 , 43 , 44 ]. Such aspects are frequently overlooked, though research has shown that they provide neurologists with a deeper understanding of their patient’s health status [ 42 , 43 ]. Some composite outcome measures are effective for the detection of a broad range of clinical manifestations and can be more sensitive than measuring a single outcome such as an MRI endpoint, relapse, or disability level [ 24 ].…”
Section: The Importance and Potential Challenges Of Early Identificat...mentioning
confidence: 99%
“…Multiple sclerosis (MS) is a chronic, progressive, inflammatory, and neurological disease [1][2][3][4] which is often accompanied by a large spectrum of clinical symptoms that include fatigue [5], sleep disturbance [5], pain or discomfort [4], social isolation [6], motor difficulties [7], cognitive impairment [8,9], hippocampal atrophy [10], and several others. According to the data available in the Atlas of MS [11] for 2020, there are 2.8 million people living with MS worldwide.…”
Section: Introductionmentioning
confidence: 99%